Worldwide incidence and prevalence of inflammatory bowel disease in the 21st century: a systematic review of population-based studies. Issue 10114 (23rd December 2017) - Ng, Siew C; Shi, Hai Yun; Hamidi, Nima; Underwood, Fox E; Tang, Whitney; Benchimol, Eric I; Panaccione, Remo; Ghosh, Subrata; Wu, Justin C Y; Chan, Francis K L; Sung, Joseph J Y; Kaplan, Gilaad G
Summary: Background: Inflammatory bowel disease is a global disease in the 21st century. We aimed to assess the changing incidence and prevalence of inflammatory bowel disease around the world. Methods: We searched MEDLINE and Embase up to and including Dec 31, 2016, to identify observational, population-based studies reporting the incidence or prevalence of Crohn's disease or ulcerative colitis from 1990 or later. A study was regarded as population-based if it involved all residents within a specific area and the patients were representative of that area. To be included in the systematic review, ulcerative colitis and Crohn's disease needed to be reported separately. Studies that did not report original data and studies that reported only the incidence or prevalence of paediatric-onset inflammatory bowel disease (diagnosis at age <16 years) were excluded. We created choropleth maps for the incidence (119 studies) and prevalence (69 studies) of Crohn's disease and ulcerative colitis. We used temporal trend analyses to report changes as an annual percentage change (APC) with 95% CI. Findings: We identified 147 studies that were eligible for final inclusion in the systematic review, including 119 studies of incidence and 69 studies of prevalence. The highest reported prevalence values were in Europe (ulcerative colitis 505 per 100 000 in Norway; Crohn's disease 322 per 100 000 in Germany) and North America (ulcerative colitis 286 per 100 000 in the USA; Crohn's disease 319 per 100 000 in Canada). The prevalence of inflammatory bowel disease exceeded 0·3% in North America, Oceania, and many countries in Europe. Overall, 16 (72·7%) of 22 studies on Crohn's disease and 15 (83·3%) of 18 studies on ulcerative colitis reported stable or decreasing incidence of inflammatory bowel disease in North America and Europe. Since 1990, incidence has been rising in newly industrialised countries in Africa, Asia, and South America, including Brazil (APC for Crohn's disease +11·1% [95% CI 4·8–17·8] and APC for ulcerative colitis +14·9% [10·4–19·6]) and Taiwan (APC for Crohn's disease +4·0% [1·0–7·1] and APC for ulcerative colitis +4·8% [1·8–8·0]). Interpretation: At the turn of the 21st century, inflammatory bowel disease has become a global disease with accelerating incidence in newly industrialised countries whose societies have become more westernised. Although incidence is stabilising in western countries, burden remains high as prevalence surpasses 0·3%. These data highlight the need for research into prevention of inflammatory bowel disease and innovations in health-care systems to manage this complex and costly disease. Funding: None.